Droplet and Spray Transport: Paradigms and Applications (Energy, Environment, and Sustainability,, 2018)
This book focuses on droplets and sprays and their applications. It discusses how droplet level transport is central to a multitude of applications and how droplet level manipulation and control can enhance the efficiency and design of multiphase systems. Droplets and sprays are ubiquitous in a variety of multiphase and multiscale applications in surface patterning, oil recovery, combustion, atomization, spray drying, thermal barrier coating, renewable energy, and electronic cooling, to name but a few. This book provides two levels of details pertaining to such applications. Each chapter delves into a specific application and provides not only an overview but also detailed physical insights into the application mechanism from the point of view of droplets and sprays. All chapters provide a mix of cutting-edge applications, new diagnostic techniques and modern computational methodologies, as well as the fundamental physical mechanism involved in each application. Taken together, the chapters provide a translational perspective on these applications, from basic transport processes to optimization, and from design to implementation using droplets or sprays as fundamental building blocks. Given its breadth of coverage, the book will be of interest to students, researchers, and industry professionals alike.